A carrier-based unbalanced PWM method for four-leg voltage source inverter fed unsymmetrical two-phase induction motor - Kumsuwan Y. (2014)
This paper presents a carrier-based unbalanced pulsewidth-modulated method for a two-phase four-leg voltage source inverter (VSI) and its realization for an unsymmetrical two-phase induction motor. A modulation strategy is developed to synthesize unbalanced two-phase output voltage waveforms based on the unipolar modulation technique with open-loop $V/f$ control. The proposed control scheme allows independent magnitude controllability and quadrature phase angle for unbalanced two-phase output voltages. Thus, the modulation algorithm makes the four-leg VSI inequitable with unbalanced two-phase loads. Simulation and experimental results confirm the feasibility of the control method for the inverter. © 2012 IEEE.